Gerakan literasi masyarakat Kabupaten Bandung - Asep Saeful Rohman; Elnovani Lusiana (Shaut Al-Maktabah : Jurnal Perpustakaan, Arsip dan Dokumentasi, 2017)
This study aims to determine the movement and literacy activities of the community in the District of Bandung. The focus of this research is on how the activity of literacy done by the community through the activity in Taman Bacaan Masyarakat (TBM). The scope of this research is about the role of TBM managers, attention to the problems of community literacy, community response to literacy movement and how the role of related parties such as government, regional libraries and others in supporting the literacy movement developed in TBM. The method used is qualitative method with case study approach. Data were collected through observation and indepth interviews. The result of this research is to get the picture that TBM-TBM managed by informants is TBM-TBM active in growing movement of literacy. Various literacy activities are actively carried out in various forms such as reading activities, discussions, workshops, training, competitions, exhibitions and storytelling. TBM managers actively inflame the literacy movement within the surrounding community. Community participation is quite high considering that the manager of TBM always actively make efforts of community involvement. Support from the government, especially the District Library Bandung is felt very meaningful and beneficial for the continuity of TBM and literacy movement. The partnership network is built actively with various parties, both government and private. The informants in the study as a whole are open to collaborating and sharing information, knowledge and experience in managing TBM and developing literacy movements in their communities.